Avaliação da aprendizagem motora por meio de dispositivo móvel e relação com a ansiedade em adultos jovens: ensaio clínico randomizado - Silva, Ana Karolina Aparecida (2021)
Introduction: Motor learning (MA) is characterized by permanent internal changes in the individual's ability to perform tasks, which can be influenced by several factors, including emotional ones, such as anxiety. To assess AM, performance curves obtained in a task are used, since direct measurement cannot be performed because it involves cognitive and motor processes. One of the instruments used in AM assessment is the Trail Making Test (TMT), initially developed for manual execution and adapted in different ways for mobile devices Objective: Evaluate AM through the trail test adapted for mobile devices and correlate the data with the level of anxiety in university students of the Physiotherapy Course. Method: Thirty-three female students from the physiotherapy course at the Federal University of Alfenas (UNIFAL-MG), between 18 and 25 years old, declared right-handed, were recruited via e-mail. These were randomized by an independent researcher into two groups, 17 in group 1 (G1) and 16 participants in group 2 (G2). Each group performed a part of the trail test, adapted to a digital version by the Computer Science department at UNIFAL-MG to assess AM in this study. The participants' level of anxiety was assessed using the State-Trait Anxiety Inventory (STAI), which was correlated with the variables related to BF (time of execution and number of errors). For statistical analysis, the Statistical Package for Social Sciences (SPSS) version 20.0 was used. The Komolgorov-Smirnov test was used to verify data normality. Subsequently, the non-parametric Friedman test was used, followed by the Wilcoxon test, to analyze the variables time and error between groups and between environments in each group. For the correlation of trait-anxiety with time and error, the Spearman correlation test was used. In all cases, p values ​​≤ 0.05 were considered significant. Results: The analysis of the characterization of the sample, considering the variables age, declared dominance, semester of the physiotherapy course, type of device used, presence and type of health problems, dominance test, IDATE-state and IDATE-trait, showed absence of statistical difference between the groups. In the intergroup evaluation, considering the time and error variables in each environment, significant values ​​(p≤0.05) were observed in the execution time for environments 1, 4 and 6 and in the number of errors for environments 1, 4 and 5. In the assessment in each group, Spearman's test showed a moderate positive correlation between IDATE-trait and error in environments 2 and 4 of group 2. In the assessment in each group, for G1 there was significance between almost all environments in the variable time, except for comparisons 1- 2, 5-6, 6-8 and 7-8. Regarding the error variable, significance was observed in the comparison 1-6, 7-8, 2-3, 7-8, 3-7, 4-7 and 5-7. For G2, in relation to the time variable, there was significance in the comparison 1–4, 5, 6, 7 and 8, 2-3, 4, 5, 6, 7 and 8, 3-4, 5, 6, 7 and 8, 4 - 5, 6, 7 and 8 and in relation to the error variable, in the comparison 1-2, 2-3, 4, 5, 6, 7 and 8. Conclusion: It is concluded that the use of trails reflects the aspects of BF, and that task difficulty, as well as anxiety directly influence BF. And that this study serves as a starting point for further studies using this methodology to assess and treat BF-related disorders.